Flash + After Effects : add broadcast features to your flash designs - Jackson, Chris (Chris B.); ScienceDirect eBooks (Oxford : Focal, 2010)
Flash Designers: push Flash to the next level with After Effects' robust toolset. CS5 delivers more complete integration of these two powerhouse applications-so you can expand your multimedia horizons. Flash + After Effects gives you a working understanding of the AE toolset and professional techniques that raise the design bar for web, HD broadcast, or CD/DVD delivery.
Part I: Bridging Flash and After Effects: Getting Started in After Effects -- Part II: Enhancing Flash Through After Effects: Alpha Channels.
Previous edition: 2008.
Includes index.
Print version record.
Safari Books Online
Elsevier
Keywords: Flash (Computer file); Adobe After effects; Adobe After effects; Flash (Computer file); Electronic books